THE USE OF THE FLIPPED CLASSROOM METHOD TO IMPROVE STUDENTS' LEARNING OUTCOMES - Achmad, Abdul Kholid; Rosidah, Amilatur (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
Learning outcomes are crucial for students, as they reflect their readiness to become lifelong learners and overcome challenges in the modern era. This study aims to improve students' learning outcomes through the flipped classroom method. The research was conducted at SMP Muhammadiyah 1 Gresik with Grade VII B students. It employed a classroom action research design consisting of several stages: pre-cycle, Cycle I, and Cycle II. The process included the following steps: (1) the teacher plans the lesson, (2) the teacher implements the flipped classroom model by reviewing previously delivered material before introducing new content, (3) students are instructed to form groups, (4) the flipped classroom model is used to provide practice questions, and (5) the teacher reflects on the learning process. The results indicate that implementing the flipped classroom method led to an 85% improvement compared to the initial 60%. This demonstrates that the flipped classroom method significantly enhances students' learning outcomes.